Investigating the expressions of miRNA-125b and TP53 in endometriosis. Does it underlie cancer-like features of endometriosis? A case-control study - Elnaz Hajimaqsoudi; Farzaneh Darbeheshti; Seyed Mehdi Kalantar; Atiyeh Javaheri; Seyed Hamidreza Mirabutalebi; Mohammad Hasan Sheikhha (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Endometriosis is generally considered as a benign condition; however, there is a possibility for it to become cancerous. miR-125b is upregulated in both endometriotic tissues and serum samples of women with endometriosis but its potential targets in endometriosis are still not fully understood. Objective: The role of miR-125b in the regulation of TP53 expression in endometriosis was tested with a bioinformatics approach. In addition, the expression of miR-125b and TP53 in both eutopic (Eu-p) and ectopic endometrium (Ec-p) in the endometrium tissues of women with endometriosis was compared to those in the normal endometrium tissues of controls (Normal). Materials and Methods: In this case-control study, the Eu-p and Ec-p samples were collected from 20 women who underwent laparoscopic surgery, and the normal endometrium tissues were collected from 20 controls with no evidence of endometriosis. For bioinformatics approach, a protein-protein interaction network was constructed based on co-expressed potential targets of miR-125b. Quantitative polymerase chain reaction technique was used for the measurement of miR125b and TP53 expression. Results: Our results showed that miR-125b was significantly overexpressed in Ec-p (p-value: 0.021). In addition, there was a significant TP53 under expression in both the Ec-p and Eu-p samples compared with the Normal tissues (p-value: 0.003). Conclusion: The negative correlation between miR-125b and TP53 as well as a noticeable decreased expression of TP53 in both Ec-p and Eu-p samples may be interpreted as the roles of miR-125b/TP53 axis in the pathogenesis of endometriosis. In addition, these findings and bioinformatic analyses imply a possible role of miR-125b in cancer-like features of endometriosis.